Are cryptocurrencies safe havens during the COVID-19 pandemic? A threshold regression perspective with pandemic-related benchmarks - Barbu, Teodora Cristina; Boitan, Iustina Alina; Cepoi, Cosmin-Octavian (Economics and Business Review, 2022)
The paper employs a threshold regression framework conditioned by two COVID-19 related proxies, to investigate whether Bitcoin and Ether exhibit short-term safe haven or diversifier features for stock and bond markets. Both cryptocurrencies fulfil a diversifier role for the responsible investments represented by sustainable stock market indices, a safe haven role for major bond markets and a mixed role for a selection of representative stock market indices. Furthermore, in times characterized by an increasing number of COVID-19 daily cases or deaths the statistical relationship between both cryptocurrencies and the main financial market determinants weakens.